Relationship between Chemical Characteristics and Sensory Evaluation of Koikuchi Soy Sauce. (22nd September 2018) - Wang, Shuo; Zhang, Han; Liu, Xiaofang; Tamura, Takehiro; Kyouno, Nobuyuki; Chen, Jie Yu
ABSTRACT: Understanding the effect of chemical characteristics on sensory evaluation elucidates the classification of soy sauce quality. In this work, 16 koikuchi soy sauces (the major form of Japanese soy sauce) from the Akita Prefectural Miso and Soy Sauce Products Committee were comprehensively studied. The results suggested that good quality soy sauce should possess a color with relatively high + a * and + b * values. Moreover, the ratio between the + L * value and + C * value had a negative influence on the external appearance. Furthermore, the soluble salt-free solids content of high-ranking soy sauce was much higher than that of low-ranking soy sauce, especially in the top three ranked soy sauces (at greater than 40%). The salt content not only negatively affect the soy sauce taste, but also played an essential role in improving the soy sauce flavor. Further study of the amino acid content showed that the glutamic acid content in high-ranking soy sauces was significantly lower than that in low-ranking soy sauces. In particular, the interaction between proline and glucose was also observed to improve soy sauce aroma. Finally, the principal component analysis was performed to reconfirm the main attributes for the sensory classification.